Reducing environmental hazards through reserve supply chain model - Shamsuddoha, M.; Quaddus, Mohammed; Klass, Desmond (World Business Institute Australia, 2011)
Environmental hazards transpire when industrial wastages are dumped illegally into vacant lands, rivers or low-lying areas. This is a major problem in developing, and less-developed countries where environmental regulations are not (or cannot be) strictly enforced. Researchers around the globe are conducting research to find various ways to minimize or eliminate industrial hazards. In this paper, we take a supply-chain approach and show how the concept of the reverse supply chain can be used to recycle industrial wastage into useful by-products. Our problem domain is poultry industry in Bangladesh. Using Simul8, a simulation model of reverse supply chain is developed for a large poultry plant in Bangladesh where poultry wastes are modelled to turn into various by-products. We use primary and secondary data to run the simulation model. Our results show that poultry wastes can indeed be processed to turn into various by products as bakery products, biogas, artificial charcoal, etc. The management of the poultry plant can use our results to develop policies to reduce poultry hazards and thus save the environment. We touch on research and managerial implications of our results.